2020
DOI: 10.3390/app10082706
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Mercury Removal over CeO2/TiO2 Catalyst Prepared by Sol–Gel Method

Abstract: Elemental mercury (Hg0) emitted from a coal-fired boiler is a serious menace and challenge to humans. Using high-efficiency CeO2/TiO2 catalysts to enhance the conversion from elemental mercury to oxidized mercury is a promising approach to reducing Hg0 emission. However, most of the CeO2/TiO2 catalysts were prepared by impregnation method or coprecipitation method while little attention has been paid to sol–gel method, which has many advantages in material production. In this study, a series of catalysts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This may be because the catalyst synthesized by the sol–gel method has a large specific surface area and abundant surface chemisorption oxygen, which are of great significance to the catalytic activity of the catalyst . Similarly, some researchers also revealed that the catalysts synthesized by the sol–gel method exhibited superior catalytic performance for Hg 0 oxidation . For the Mn-VWTi catalyst, the addition of Mn could enhance the Hg 0 oxidation activity of the catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because the catalyst synthesized by the sol–gel method has a large specific surface area and abundant surface chemisorption oxygen, which are of great significance to the catalytic activity of the catalyst . Similarly, some researchers also revealed that the catalysts synthesized by the sol–gel method exhibited superior catalytic performance for Hg 0 oxidation . For the Mn-VWTi catalyst, the addition of Mn could enhance the Hg 0 oxidation activity of the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…28 Similarly, some researchers also revealed that the catalysts synthesized by the sol−gel method exhibited superior catalytic performance for Hg 0 oxidation. 29 For the Mn-VWTi catalyst, the addition of Mn could enhance the Hg 0 oxidation activity of the catalysts. For instance, more than 95% of E oxi could be achieved over Mn 3 -VWTi catalyst at 200−350 °C.…”
Section: Effects Of Mn Contents Onmentioning
confidence: 99%
“…In addition to indirectly promoting mercury oxidation, the OCs may also react directly with Hg 0 . Previous studies showed that lattice oxygen in metal oxides can be converted into surface reactive oxygen species and then oxidize elemental mercury directly. Perez-Vega et al found that copper oxide in OCs significantly promoted the heterogeneous oxidation reaction of Hg 0 . Besides, Mendiara et al pointed out that the pore structure of the OCs provides adsorption sites for gas-phase Hg 0 .…”
Section: Introductionmentioning
confidence: 99%
“…The removal difficulty varies for different forms of mercury. Elemental mercury (Hg 0 ), with low solubility and high volatility, is the most difficult to remove, while oxidized mercury (Hg 2+ ) and particulate mercury (Hg p ) are relatively easier to remove [12,13]. Therefore, promoting the transformation of Hg 0 to Hg 2+ and Hg p is the key to realizing deep mercury removal.…”
Section: Introductionmentioning
confidence: 99%